Intra-atrial calcium infusions, growth, and development in end organ resistance to vitamin D. Issue 6 (December 1993) - Lin, J P; Uttley, W S
Abstract : A five and a half year follow up of a girl with end organ resistant rickets is described. After failing to respond to high dose oral alfacalcidol (4 micrograms/kg/day) and calcium supplements, treatment for one year with domiciliary intra-atrial calcium infusions at 2 years of age induced a complete remission, which was maintained on subsequent high dose oral calcium supplement. Overnight infusions were well tolerated without adverse cardiovascular or renal sequelae or ectopic calcification. If the first three years of life are survived, the prognosis for a normal life on oral treatment is excellent.